1995
DOI: 10.1002/jmv.1890470422
|View full text |Cite
|
Sign up to set email alerts
|

Serological and salivary markers compared with biochemical markers for monitoring interferon treatment for hepatitis C virus infection

Abstract: Paired serum and saliva specimens were collected on a regular basis from 18 asymptomatic blood donors participating in a controlled clinical trial of interferon alpha 2a (IFN) treatment of chronic hepatitis C virus (HCV) infection. Nine patients were randomised to receive interferon and nine to observation only. Serum and salivary HCV RNA was detected by a "nested" polymerase chain reaction (PCR) assay. Complete follow-up data were available for 14 patients (7 treated and 7 untreated). Serum ALT levels decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
2
5
1
Order By: Relevance
“…In a paper by Roy et al. (6) HCV‐RNA clearance was detected in the saliva of two treated patients who did not respond to IFN, which corresponds with our pattern 3b. Nevertheless, patterns 3a and 3b are contradictory, and could not be justified with this argument.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In a paper by Roy et al. (6) HCV‐RNA clearance was detected in the saliva of two treated patients who did not respond to IFN, which corresponds with our pattern 3b. Nevertheless, patterns 3a and 3b are contradictory, and could not be justified with this argument.…”
Section: Discussionsupporting
confidence: 89%
“…It has been suggested that monitoring the effect of IFN by evaluating HCV‐RNA in saliva has not shown a direct relationship with HCV in blood (6). In agreement with these authors, the description of three different HCV clearance patterns in saliva of patients with chronic HCV infection under interferon plus ribavirin therapy has been made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was extracted from 200 l of serum and saliva using the QIAamp blood kit (QIAGEN, Surrey, UK) according to the manufacturer's instructions, with the addition of carrier RNA (1 g/ml) (GIBCO-BRL, Life Technologies, Paisley, Scotland) and 1 unit of RNA guard (Pharmacia, Herts, UK). Reverse transcription and PCR using primers derived from the 5Ј non-coding region (NCR) was carried out as previously described [Roy et al, 1995]. Briefly, synthesis of cDNA from 10 l RNA was carried out at 37°C for 30 min with 200 units of Moloney Murine Leukaemia Virus (MMLV) reverse transcriptase (GIBCO-BRL) in 20 l buffer containing 50 mM KCl, 2.5 mM MgCl 2 , 20 mM Tris-HCl pH 8.4, 0.1 mM (each) dNTP and 1 unit of RNA guard (Pharmacia).…”
Section: Rna Extraction and Pcrmentioning
confidence: 99%
“…The various studies that have compared viral load with the presence of HCV-RNA in the saliva have shown both positive [9,15,23,27] and negative correlations [10,28]. We did not evaluate this association.…”
Section: Discussionmentioning
confidence: 97%